Quantum‐tative Finance. Issue 106 (23rd March 2020) - Orrell, David
Abstract : Finance is quantum. David Orrell doesn't mean this in a metaphorical sense ‐ as in "let's imagine that traders are like electrons" ‐ but in the sense of a mathematical model.